The role of organizational culture in improving employee performance through organizational commitment - Sumarjo, Wahid; Haerofiatna, Haerofiatna; Wahyudi, Wahyudi (Institute of Computer Science (IOCS), 2025)
One factor that propels organizational success is employee performance. Because it has a direct effect on the company's overall growth and profitability, subpar employee performance can have a big influence on its success. Missed deadlines, reduced productivity, and more mistakes may result from an employee not performing up to expectations. Long-term profitability and the organization's general success will be impacted by all of that. Through organizational commitment, this study seeks to examine how organizational culture affects employee performance. This study was carried out at PT Arwana Citra Mulia Tbk, which has 74 employees. A quantitative technique using the PLS-SEM methodology is employed. According to the study's findings, organizational culture influences both organizational commitment and personnel performance. Enhancing the organization is strongly influenced by organizational commitment, which can also act as a mediator between enhancing employee performance and organizational culture